State and agents in China : disciplining government officials - Cai, Yongshun (Stanford University Press, 2015)
Chinese government officials have played a crucial role in China's economic development, but they are also responsible for severe problems, including environmental pollution, violation of citizens' rights, failure in governance, and corruption. How does the Chinese Party-state respond when a government official commits a duty-related malfeasance or criminal activity? And how does it balance the potential political costs of disciplining its own agents versus the loss of legitimacy in tolerating their misdeeds? State and Agents in China explores how the party-state addresses this dilemma, uncove.